Motives behind the implementation of renewable energy sources in South African businesses - Smith, Brendon Michael (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
There are numerous advantages and disadvantages for companies to implement renewable energy in South Africa. The motives (drivers or challenges) behind the decision to implement renewable energy resources or not is what this research will be addressing. Economic and environmental motives were the major motives behind implementing renewable energy sources in literature. The main objective for this research was to identify and describe the motives and challenges of implementing renewable energy sources in SA businesses, aligning these with sustainability pillars. The data collection method that was used in this research was documentation analysis and questionnaires. The companies that were chosen for this research were sampled from Kwa-Zulu Natal. Results showed that economic motives were the main decisions for companies implementing renewable energy or not, although there were also significant environmental and social motives that businesses need to consider. This research has provided an understanding of the motives that can have a positive or negative impact on companies who want to install renewable energy for their business.
Keywords: Uncatalogued